Analysis Of Pavement Improvement Planning For the Lumajang City Boundary Road Section – BTS, Jember District - Rendy Zesario Akbar; Budi Witjaksana; Jaka Purnama (Syntax Corporation Indonesia, 2025)
Road damage is a common issue that arises due to various factors, including substandard construction quality, overloaded vehicles, and extreme weather conditions. The road segment connecting Lumajang City Limits to Jember District Limits has been identified as experiencing deterioration at several locations, predominantly caused by vehicles carrying loads that exceed the maximum allowable capacity. This study focuses on evaluating the current condition of the road, estimating the required repair costs, and assessing the economic feasibility of implementing the repairs. The research methodology incorporates field surveys to gather primary data, such as the extent, severity, and distribution of road damage, along with secondary data on traffic volumes and vehicle loads. The analysis involves classifying road conditions and calculating repair costs using the overlay method, which considers structural improvements needed to restore optimal functionality. The results indicate that out of the total road length, 1.66 kilometers are classified as being in good condition, 1.3 kilometers are in fair condition, 7.2 kilometers have minor damage, and 4 kilometers are severely damaged. These findings provide essential insights for prioritizing repair works and formulating cost-effective strategies to improve road infrastructure in the region.